The grape powdery mildew resistance loci Ren2, Ren3, Ren4D, Ren4U, Run1, Run1.2b, Run2.1, and Run2.2 activate different transcriptional responses to Erysiphe necator - Massonnet, Mélanie; Riaz, Summaira; Pap, Dániel; Figueroa-Balderas, Rosa; Walker, M. Andrew; Cantu, Dario (Frontiers in Plant Science, 2022)
Multiple grape powdery mildew (PM) genetic resistance (R) loci have been found in wild grape species. Little is known about the defense responses associated with each R locus. In this study, we compare the defense mechanisms associated with PM resistance in interspecific crosses segregating for a single R locus from Muscadinia rotundifolia (Run1, Run1.2b, Run2.1, Run2.2), Vitis cinerea (Ren2), V. romanetii (Ren4D and Ren4U), and the interspecific hybrid Villard blanc (Ren3). By combining optical microscopy, visual scoring, and biomass estimation, we show that the eight R loci confer resistance by limiting infection at different stages. We assessed the defense mechanisms triggered in response to PM at 1 and 5 days post inoculation (dpi) via RNA sequencing. To account for the genetic differences between species, we developed for each accession a diploid synthetic reference transcriptome by incorporating into the PN40024 reference homozygous and heterozygous sequence variants and de novo assembled transcripts. Most of the R loci exhibited a higher number of differentially expressed genes (DEGs) associated with PM resistance at 1 dpi compared to 5 dpi, suggesting that PM resistance is mostly associated with an early transcriptional reprogramming. Comparison of the PM resistance-associated DEGs showed a limited overlap between pairs of R loci, and nearly half of the DEGs were specific to a single R locus. The largest overlap of PM resistance-associated DEGs was found between Ren3+, Ren4D+, and Ren4U+ genotypes at 1 dpi, and between Ren4U+ and Run1+ accessions at 5 dpi. The Ren3+, Ren4D+, and Ren4U+ were also found to have the highest number of R locus-specific DEGs in response to PM. Both shared and R locus-specific DEGs included genes from different defense-related categories, indicating that the presence of E. necator triggered distinct transcriptional responses in the eight R loci.